Reusable plasmonic substrates fabricated by interference lithography: a platform for systematic sensing studies - Siegfried, Thomas; Kind, Martin; Terfort, Andreas; Martin, Olivier J. F.; Zharnikov, Michael; Ballav, Nirmalya; Sigg, Hans (Journal of Raman spectroscopy, 2013)
Surface-enhanced Raman scattering (SERS) has become increasingly popular in the scientific and industrial communities because of its analytical capabilities and potential to study fundamentals in plasmonics. Although under certain conditions extremely high sensitivity is possible, the practical use of SERS is frequently limited by instability and poor reproducibility of the enhancement factor. For analytical applications or for comparative measurements to enable the distinction between electromagnetic and chemical enhancement, the development of standardized and recyclable SERS substrates, having uniform and persistent performance, is proposed. To this end, we have fabricated periodic nanoslit arrays using extreme ultraviolet lithography that provide average large (2*106) and homogeneous SERS enhancement factors with a spot-to-spot variability of less than 3%. In addition, they are reusable without any degradation or loss of enhancement. The fabrication of such arrays consists of two steps only, lithographic patterning followed by metal evaporation. Both processes may be performed over areas of several square mm on any planar substrate. The sensor capabilities were demonstrated by substrates with monomolecular films of several different thiols. The concept of reusable SERS substrates may open a powerful platform within an analytical tool and in particular for systematic SERS studies for the investigation of fundamental parameters such as chemical enhancement, surface selection rules, and molecular alignment. Copyright © 2012 John Wiley & Sons, Ltd.
Published online: 31 August 2012
Gesehen am 27.01.2022